The role of citizenship education management in facing the challenges of multiculturalism - Dadang Mulyana (Sean Institute, 2024)
Multiculturalism is a complex reality that requires a careful approach in managing citizenship education. This study will focus on how civic education management can effectively manage the challenges that arise due to cultural, ethnic and religious diversity in the educational context. This research aims to investigate the role of civic education management in facing the challenges of multiculturalism in the educational environment. This research uses a qualitative approach with descriptive methods. The results of this research reveal that the implementation of Citizenship Education Management (PPKn) has a positive impact in facing the challenges of multiculturalism. Inclusive curriculum design, teacher training to manage heterogeneous classes, establishing an inclusive school environment, facilitating intercultural dialogue, and ongoing program evaluation have been proven to make significant contributions in shaping student character that is responsive to cultural diversity. The research results show that PPKn is not only a vehicle for conveying civic information, but is also effective as a tool for forming inclusive attitudes, a deep understanding of differences, and adaptability skills in a multicultural society. In conclusion, the holistic implementation of PPKn can have a positive impact on the formation of a generation that has a sense of nationality, love of the country, and is able to become an agent of positive change in an increasingly complex society.